An impetus for change? - Owen, Jayne (Br Dent J, 2021)
For years, the British Society of Paediatric Dentistry has been highlighting the shortage of specialists in paediatric dentistry in the UK and the consequent inadequacy of provision of, and inequality of access to, specialist care. This is a problem which must be addressed nationally. The aim of this article is to understand the obstacles to change and the impact of this continuing shortage, with a particular focus on the decline in the numbers of non-consultant specialists. I will examine the challenges and possible solutions, taking into account the impact of COVID-19 on service delivery.